A142 IMPACT OF HLADQA1*05G>A GENETIC-SCREENING FOR OPTIMAL ANTI-TNF THERAPY IN INFLAMMATORY BOWEL DISEASE: A PRELIMINARY REPORT. (21st February 2022) - Wilson, A; Chande, N; Ponich, T; Gregor, J C; Khanna, R; McIntosh, K; Sey, M; Beaton, M D; Kim, R B
Abstract: Background: Genetic variation in the human leukocyte antigen ( HLA ) gene is strongly associated with the formation of anti-drug antibodies to tumor necrosis factor-alpha antagonists (anti-TNF) in inflammatory bowel disease (IBD). It is also associated anti-TNF loss of response and treatment discontinuation. Aims: We aimed to evaluate the utility of preemptive HLADQA1*05G>A screening to reduce the incidence of treatment-related adverse events in an IBD population by lessening the need for combination therapy in those who do not carry the risk allele. We also assessed for the occurrence of anti-TNF anti-drug antibody (ADA) formation, anti-TNF loss of response, treatment discontinuation compared to an unscreened population. Methods: A non-randomized open label study is ongoing in IBD patients being considered for anti-TNF therapy. Participants received either pre-treatment HLADQA1*05G>A screening (prospective-screening group, n=25/110 recruited), with the addition of one of azathioprine or methotrexate to anti-TNF therapy (combination therapy) if identified as a high risk variant carrier (G/A or A/A) or received combination therapy without undergoing prospective HLADQA1*05A>G screening (control group, n=25/110 recruited). All participants will be followed for up to 1 year and observed for the occurrence of any adverse drug events, formation of anti-TNF drug antibodies (ADA), anti-TNF loss of response and anti-TNF discontinuation. Results: To date, the prevalence of HLADQA1*05 G/A and A/A was 20% in the prospective-screening group and thus 20% (n=5/25) received combination therapy and 80% (n=20) received anti-TNF monotherapy. All participants in the control group (n=25/25) received combination therapy. Considering all groups, 78% (n=39/50) received infliximab, while 22% (n=11/50) received adalimumab. To date, the median follow-up period is 5 (IQR=4) months. Fewer adverse drug events have been reported in the prospective-screening group versus the control group (16.7% vs 33.3%, odds ratio 0.40, 95%CI=0.12–1.56, p=0.18). Anti-TNF ADA formation and treatment discontinuation were similar between groups (prospective-screening, 0% versus control, 4.2%). A higher proportion of controls experienced anti-TNF loss of response (16.7% vs 8.3%, p=0.38). Conclusions: Preemptive HLADQA1*05G>A screening appears to reduce the need for combination therapy when using anti-TNF agents in an IBD population. Fewer drug-related adverse events are reported to date in the screened cohort without a concomitant increase in deleterious outcomes such as ADA formation or anti-TNF discontinuation. Completion of this study will help define whether or not HLADQA1*05G>A -screening is a clinically-actionable and relevant tool for guiding the application of combination therapy in IBD. Funding Agencies: Lawson Health Research Institute